2010
DOI: 10.1002/lary.20845
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topical castellani solution on outer hair cell function of rats

Abstract: In the rat, Castellani solution, which is topically applied to the middle ear cavity, does not affect DPOAE amplitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Topical ear drops have many advantages over systemic treatments (12). Topical application may be performed at high concentrations in the relevant area in addition to the fact that it does not cause side effects such as diarrhea, nausea, vomiting, and rash.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical ear drops have many advantages over systemic treatments (12). Topical application may be performed at high concentrations in the relevant area in addition to the fact that it does not cause side effects such as diarrhea, nausea, vomiting, and rash.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of animal model studies have been used for investigating possible ototoxic effects of topical ear drops in the presence of perforation (13). In rodent models, the effects of many topical antibiotics have been investigated; in particular, gentamicin has been found to be consistently and significantly ototoxic (12)(13)(14). Therefore, in our study, we used gentamicin as the positive control group.…”
Section: Discussionmentioning
confidence: 99%
“…The ototoxicity of Castellani's solution has been less investigated than that of Burow's solution [13] . Gültekin et al [13] have demonstrated that Castellani's solution has no toxic effects on the functioning of outer hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gültekin et al [13] have demonstrated that Castellani's solution has no toxic effects on the functioning of outer hair cells. In the literature, no study researching the effect of Castellani's solution on the middle ear mucosa appears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation